A socio‐economic theory of regulatory compliance - Sutinen, Jon G.; Kuperan, K. (Emerald, 1999)
An enriched theoretical model of regulatory compliance is developed in this paper. The body of empirical evidence demonstrates that the pure deterrence model of regulatory compliance, which focuses primarily on the certainty and severity of sanctions as key determinants of compliance, provides only a partial explanation of compliance behavior. To offer a more complete explanation, the model developed herein integrates economic theory with theories from psychology and sociology to account for both tangible and intangible motivations influencing individuals’ decisions whether to comply with a given set of regulations. Specifically, the model accounts for moral obligation and social influence in addition to the conventional costs and revenues associated with illegal behavior. While cast in a natural resource management context, the theory developed here is applicable to a variety of institutional conditions. The resulting framework enables the design and implementation of more efficient compliance and regulatory programs than was heretofore possible.